(untitled) (Journal of Architectural Design, 2025)
This article is devoted to the importance of pre-design work in the construction of university campuses. It examines the key stages of preparation that ensure the successful implementation of the project and the creation of a comfortable environment for learning and research. The main focus is on analyzing the needs of students and teachers, monitoring the territory, environmental assessment, general planning, infrastructure and architecture design, as well as social and cultural research. The importance of community engagement and financial resource assessment is emphasized to ensure the sustainable development and effectiveness of the campus. The article summarizes the importance of a systematic approach to pre-design work as the basis for creating a functional and harmonious educational space.